Critical mass - Martini, Steve (New York : G.P. Putnam's Sons, 1998)
Burned-out lawyer Joss Cole finds her new life turned upside down when her client is murdered and the trail leads to two missing nuclear devices and a deadly terrorist plot, and involves her with nuclear expert Gideon Van Ry.
73388
Keywords: Women lawyers -- Fiction. -- Washington (State) -- San Juan Islands; Radioactive substances -- Fiction; Nuclear terrorism -- Fiction; San Juan Islands (Wash.) -- Fiction; Adventure stories